SISTEM PENYIMPANAN DAYA LISTRIK DENGAN MENGGUNAKAN ACCU 12 VOLT SECARA OTOMATIS - Hasbi Assiddiq S (LPPM Politeknik LP3I Medan, 2019)
Because electricity is supplied by the National Electric Company, sometimes there is a power outage which results in obstruction of community activities, especially in the household sector at night which is very unfortunate when there is a blackout. This research was conducted to build an electrical power storage system design for lighting that can be used as a power supply when an unexpected power outage occurs. Then after making the circuit is complete then testing is carried out with the aim of knowing the working principle of the circuit and knowing batteries resistance as a means of storing electric power. The components used in this series are one batteries 12 Volt / 3.5 Ah as an electric power storage device, two relays as automatic switches in the circuit, three LED lights in the form of LED modules with a power value of 0.96 Watt each (as many as two) and 0.8 Watts, one CT transformer as batteries charging circuit, one ampere meter to monitor the current value when batteries is charging, and two MCB with a value of 6 Ampere as safety circuit. The result of the research that has been done is that batteries as an electric power storage device can last up to 14 hours 50 minutes with the largest load value of 2.72 Watts.